Experimental investigation on laser milling of aluminium oxide using a 30 W Q-switched Yb:YAG fiber laser. (January 2016) - Leone, C.; Genna, S.; Tagliaferri, F.; Palumbo, B.; Dix, M.
Abstract: In the present study, laser milling tests were carried out on aluminium oxide (Al2 O3 ) plate, 3 mm in thickness, using a Q-Switched 30 W Yb:YAG fiber laser. A systematic approach based on Design of Experiment (DoE) has been successfully adopted with the aim to detect which and how the process parameters affect the laser beam–material interaction, and to explain the effect of the process parameters on the material removal rate and surface quality. The examined process parameters were the laser beam scan speed, the pulse frequency, the total energy released for surface unit, the distance between two consecutive scan lines and the scanning strategy. A full factorial design and ANalysis Of VAriance (ANOVA) were applied for the results analysis. Finally, the various effects of the process parameters on the material removal rate and surface roughness have been analysed and discussed. Highlights: The research topic concerns laser milling of high performance ceramic material. The process is based on a low power and high efficiency fiber laser source. The influence of process parameters on MRR and roughness was assessed. A statistical approach (DoE and ANOVA) was adopted to increase the results robustness.